A Review of Fault Diagnosis of Induction Machines - Verucchi, Carlos (2008)
Different alternatives to detect and diagnose faults in induction machines have been proposed and implemented in the last years. These new alternatives are characterised by an on-line and non-invasive feature, that is to say, the capacity to detect faults while the machine is working and the capacity to work sensorless. These characteristics, obtained by the new techniques, distinguish them from the traditional ones, which, in most cases, need that the machine which is being analysed is not working to do the diagnosis. The main purpose of this article is to revise the main alternatives in the detection of faults in induction machines and compare their contributions according to the information they require for the diagnosis, the number and relevance of the faults that can be detected, the speed to anticipate a fault and the accuracy in the diagnosis.